Christer Bruun: The Water Supply of Ancient Rome. A Study of Roman Imperial Administration (Commentationes Humanarum Litterarum. 93), Helsinki, Societas Scientiarum Fennica. 1991, 456 pp. - CASILLAs, Juan Miguel (Gerión. Revista de Historia Antigua, 1992)
Sin resumen